Ankle and knee joint functional indices during a drop jump: exploring performance relationships - Haischer, M. H.; Ahn, N.; McKeough, N.; Adler, W. R.; Kipp, K. (ISBS Proceedings Archive (Michigan), 2023)
The purpose of this study was to describe ankle and knee joint functional indices during a drop jump task and characterize the associations to performance outcomes (jump height, ground contact time, and reactive strength index). Forty-five collegiate or club level athletes performed five drop jumps off a 12-inch box while motion capture and ground reaction force data were recorded. Time-series joint kinematics and kinetics were used to calculate joint functional indices, reported as relative percentages of strut-, spring-, damper-, and motor-like mechanical behavior. Correlation and regression analyses uncovered several significant associations between joint functional indices and performance outcomes. Greater motor-like function at the knee during a drop jump is associated with a greater reactive strength index and jump height as well as a shorter ground contact time.